2006
DOI: 10.1007/s00134-006-0082-0
|View full text |Cite
|
Sign up to set email alerts
|

Central hemodynamics during lung recruitment maneuvers at hypovolemia, normovolemia and hypervolemia. A study by echocardiography and continuous pulmonary artery flow measurements in lung-injured pigs

Abstract: In this animal lung injury model, lung recruitment maneuvers significantly decreased left-ventricular end-diastolic volume and cardiac output at hypovolemia. Hypervolemia did partly counteract this compromise. In addition, a marked right-ventricular dysfunction during the maneuver was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(26 citation statements)
references
References 29 publications
1
23
1
1
Order By: Relevance
“…29 Also, some animal studies raised concerns about hemodynamic intolerance of recruitment maneuvers. [30][31][32] In the present study we found no serious adverse hemodynamic effects, but that assessment was based on arterial blood pressure measurement, which may underestimate the effect on cardiac performance. 33…”
Section: Discussioncontrasting
confidence: 44%
“…29 Also, some animal studies raised concerns about hemodynamic intolerance of recruitment maneuvers. [30][31][32] In the present study we found no serious adverse hemodynamic effects, but that assessment was based on arterial blood pressure measurement, which may underestimate the effect on cardiac performance. 33…”
Section: Discussioncontrasting
confidence: 44%
“…Nielsen et al . [51] tested the impact of RM in hypovolemia, normovolemia and hypervolemia. Lung RMs significantly decreased left ventricular end diastolic volume as well as cardiac output during hypovolemia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the higher PaCO 2 with these settings might only be an artifact. It could also be caused by an increased alveolar dead space in overstretched lung regions, as well as compromised circulation due to the high airway pressures (31).…”
Section: Discussionmentioning
confidence: 99%
“…Second, hysteresis and shape of the PV curve might be due to other factors than pure lung and chest wall mechanics, e.g., blood volume shift and gas exchange (33). We did not compensate for gas exchange during the PV loop procedure because we estimated that its influence on the measured MH was <20 ml; the oxygen consumption in anesthetized, mechanically ventilated pigs of similar size as used in this study is about 140 ml/min, the duration of the whole procedure was <1 min, and the airway pressures used during the procedure would reduce pulmonary circulation and thus gas exchange (31, 34). Third, we have not measured chest wall compliance.…”
Section: Discussionmentioning
confidence: 99%